Post‑crisis Economic Environment of Two Central and Eastern European Regional Centres: A Comparative Approach - Zsibók, Zsuzsanna; Egyed, Ildikó (Comparative Economic Research. Central and Eastern Europe, 2022)
Our research studies the economic background of recovery and catching‑up after the global financial and economic crisis, comparing the case study areas of Cluj‑Napoca in Romania and Pécs in Hungary. We use explorative statistical data analysis to describe the post‑crisis regional economic environment in the context of the differential outcomes of the high‑pressure economy in these two countries. Then, we analyse the evolution of the per capita gross domestic product in a decomposed form which provides insights into the main challenges of regional development in the two regional centres. The results show that long‑run economic challenges must be handled with an efficiency‑oriented regional policy that relies upon capital and knowledge‑intensive growth.